(untitled) (Journal of the College of Education for Women, 2019)
Minister Yacoub Ben Keles distinguished himself with leadership and administrative talents, as well as his abilities in the field of jurisprudence, which made him the top political, administrative and cultural scene of the Fatimid state and left its mark on it by influencing its fateful decisions.He was the son of Kels of the Jews of Baghdad, where he learned writing and arithmetic, and moved with his father to Syria and then carried him to Egypt.Egypt embraced the son of Kels, living in a transitional period from the Achaishid era to the Fatimid period. Both these two covenants reconciled this man to his career until he became minister in the Fatimids in 368 A.H. / 978 A.D.His character was overshadowed by most of the state’s men, and those who were credited with the emergence of the Fatimid state in Egypt, such as the leader Jawhar al-Saqli, played an important role in the context of the internal politics of the Fatimid state. In foreign policy, the Levant occupied most of its interests, The great powers at the time exceeded his role in the Hijaz, Iraq,BaniZiridand with the Byzantines, and during the time of this minister, the Fatimid state reached its fullest extent.Upon the death of this minister, the Fatimid were keen to establish the grief of his death, and to preserve the rights of his beloved and the rights of his family and slaves, and the depth of the feelings of sorrow for his departure, but a clear proof of the majesty of this minister and his clear role in the history of their state.